2013
DOI: 10.1038/nn.3419
|View full text |Cite
|
Sign up to set email alerts
|

Neural coding during active somatosensation revealed using illusory touch

Abstract: Active sensation requires the convergence of external stimuli with representations of body movements. We used mouse behavior, electrophysiology and optogenetics to dissect the temporal interactions between whisker movement, neural activity, and sensation of touch. We photostimulated layer 4 activity in single barrels in closed-loop with whisking. Mimicking touch-related neural activity caused illusory perception of an object at a particular location, but scrambling the timing of spikes over one whisking cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
258
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(272 citation statements)
references
References 57 publications
10
258
3
1
Order By: Relevance
“…Similarly, Histed and Maunsell [104] applied photostimulation in order to investigate the contribution of pulse duration and intensity to the detectability of a direct optical stimulation of excitatory neurons in the mouse V1 and found that psychophysical performance was well predicted by the total number of spikes, induced by increased amounts of light. Similar results were obtained at the somatosensory cortex in a study which examined the effects of optogenetic stimulation of layer 4 (L4) excitatory neurons on report of illusory touch [105]. The researchers trained mice to report the position of a pole using their whiskers and then manipulated the sensation by photostimulating L4 activity.…”
Section: (B) Comparison With Microstimulation and Optogenetic Stimulasupporting
confidence: 57%
“…Similarly, Histed and Maunsell [104] applied photostimulation in order to investigate the contribution of pulse duration and intensity to the detectability of a direct optical stimulation of excitatory neurons in the mouse V1 and found that psychophysical performance was well predicted by the total number of spikes, induced by increased amounts of light. Similar results were obtained at the somatosensory cortex in a study which examined the effects of optogenetic stimulation of layer 4 (L4) excitatory neurons on report of illusory touch [105]. The researchers trained mice to report the position of a pole using their whiskers and then manipulated the sensation by photostimulating L4 activity.…”
Section: (B) Comparison With Microstimulation and Optogenetic Stimulasupporting
confidence: 57%
“…Thus, the existence and use of temporal codes may be specific only to some relay stations and pathways, possibly used for specific computations. Recent studies in auditory and somatosensory cortex show a good correlation (Bathellier et al, 2012), possibly even a causal link (Musall et al, 2014;O'Connor et al, 2013), between cortical rate codes and perception. But the simplicity of the stimuli and the behavioral model used in these studies do not exclude the possibility that cortical structures with a high information load such as primate V1 use a sparse code based on precise spike timing, as observed during high-dimensional natural-scene stimulation (Baudot et al, 2013;Vinje and Gallant, 2000).…”
Section: Dynamic Assembly Codes For Perceptionmentioning
confidence: 97%
“…As discussed below, under specific conditions of sensory drive, [67 ] also observed that FS activation could suppress performance in a similar detection task. Also, O'Connor and colleagues (2013) [77] found that optogenetic stimulation across interneuron types (using the VGAT-ChR2 promoter) also decreased stimulus-related firing rates and suppressed behavior, in this case for an active sensing vibrissal task. In the Sachidhanandam and O'Connor studies, no attempt was made to explicitly emulate FS-gamma oscillations.…”
Section: Optogenetic Drive Of Fs Interneurons Can Impair Sensory Detementioning
confidence: 97%